Feather mites of Brazil (Acari: Astigmata: Analgoidea and Pterolichoidea) - Valim, Michel P.; Hernandes, Fabio Akashi [UNESP]; Proctor, Heather C. (Taylor & Francis Inc, 2011)
We present a checklist of feather mites known from native birds in Brazil. The list was compiled from a survey of Brazilian records published in indexing databases (e.g. Zoological Records) and from the available literature. To date, 185 nominal species representing 21 families have been recorded from Brazilian birds. Associations with 15 bird orders were found: Anseriformes, Apodiformes, Caprimulgiformes, Ciconiiformes, Columbiformes, Cuculiformes, Falconiformes, Galliformes, Gruiformes, Opisthocomiformes, Passeriformes, Piciformes, Psittaciformes, Tinamiformes and Trogoniformes. These birds sum to 218 species, which represent only 12.4% of all bird species occurring in Brazil. The feather mite fauna of several species-rich and important bird orders in Brazil remain unexplored, including Cathartiformes, Charadriiformes, Coraciiformes, Galbuliformes and Strigiformes. We estimate that between 900 and 5300 feather mite species are expected to occur on Brazilian birds, which is at least five times greater than current records. The training of researchers with expertise in the taxonomy of this group of mites should be stimulated so that there is a compatible number of taxonomists to discover and describe the almost unexplored feather mite fauna in Brazil.
Keywords: Acari; feather mites; Analgoidea; Pterolichoidea; Aves; Birds; Taxonomy; Biodiversity; Neotropical region